2015
DOI: 10.1111/pcn.12360
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional anatomy of ‘modern type depression’ in Japan: A proposal for a different diagnostic approach to depression beyond the DSM‐5

Abstract: Japan's prototype of depression was traditionally a melancholic depression based on the premorbid personality known as shūchaku‐kishitsu proposed by Mitsuzo Shimoda in the 1930s. However, since around 2000, a novel form of depression has emerged among Japanese youth. Called ‘modern type depression (MTD)’ by the mass media, the term has quickly gained popularity among the general public, though it has not been regarded as an official medical term. Likewise, lack of consensus guidelines for its diagnosis and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(119 citation statements)
references
References 66 publications
2
117
0
Order By: Relevance
“…In particular, PTSD symptoms, such as irritability and outbursts of anger, as well as elevated rates of alcohol consumption in parents, may contribute to higher levels of child abuse. In line with this hypothesis, studies in post-war Sri Lanka and Uganda have shown that, next to parents' own experiences of child abuse, children's reports of maltreatment were associated with the parents' exposure to war and their PTSD symptom severity as well as with male guardian's alcohol consumption 7 .…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…In particular, PTSD symptoms, such as irritability and outbursts of anger, as well as elevated rates of alcohol consumption in parents, may contribute to higher levels of child abuse. In line with this hypothesis, studies in post-war Sri Lanka and Uganda have shown that, next to parents' own experiences of child abuse, children's reports of maltreatment were associated with the parents' exposure to war and their PTSD symptom severity as well as with male guardian's alcohol consumption 7 .…”
mentioning
confidence: 70%
“…Parent-child relationships in Japan have long been considered less oedipal than in Western societies and marked by an absent father and an extremely prolonged and close bond to the mother, which may result in difficulty to become independent 7 . Especially in hikikomori, the development of basic interpersonal skills during the early stages of life seems to be insufficient, which can induce vulnerability to stress in later school/workplace environments and lead to escape from social situations 7 .…”
Section: Claudia Catanimentioning
confidence: 99%
“…Some persons may not express depressive mood at all in order to hide internal turmoil, and others may hyperbolically show their depressed mood to obtain a sick role . These difficult situations have resulted in confusion in clinical practice [10, 11]. To our knowledge, no significant blood biomarkers to predict SOD have existed until now.…”
Section: Introductionmentioning
confidence: 99%
“…As described in a recent treatment guideline for MTD and a literature review of MTD, contents of symptoms of MTD (e.g., depressed mood) are not substantially different from those of traditional‐type depression (TTD). Rather, these studies showed that MTD is characterized by patients’ unique personality traits and specific patterns of how their symptoms are expressed in their lives. People with MTD are characterized by mood reactivity and interpersonal sensitivity and are said to express their depressive symptoms mainly during work .…”
Section: The Present Study: How Cultural Contexts Affect Perceptions mentioning
confidence: 99%